The Tradition of Using Shrouds and Acid Water During Sacrificial Animal Slaughtering in Panti Selatan Village, Panti District, Pasaman Regency: An 'Urf Perspective - Gina Raudhatul Jannah; Fauzan; Muhammad Ridha; Shafra (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
The community of Nagari Panti Selatan practices a unique tradition involving the use of shrouds (kain kafan) and acid water during the slaughtering of sacrificial animals. This tradition exhibits distinct characteristics compared to the general Islamic procedures for slaughtering sacrificial animals. This study aims to describe the implementation process of this tradition and to analyze it from the perspective of ‘urf (customary law) in Islamic jurisprudence. This research is a qualitative field study. Primary data were gathered through interviews with traditional leaders, religious figures, and relevant stakeholders, while secondary data were obtained from books, academic journals, and theses related to the research theme. Data collection methods included interviews, observation, and documentation. The findings reveal that the shroud is used before the slaughter to cover or shelter the animal (known as the unduang-unduang tradition), symbolizing the sanctity and sincerity of the ritual purely for the sake of Allah SWT. Meanwhile, the acid water (a mixture of water, lime slices, and ground rice) is used to purify the animal and is interpreted as a symbol to eliminate animalistic traits such as greed, stubbornness, and arrogance within the person offering the sacrifice. From the perspective of Islamic law, although there are no specific textual regulations regarding this practice , the tradition in Nagari Panti Selatan is categorized as ‘urf sahih (valid custom) since it embodies positive values, does not contradict Islamic law, and does not cause any harm or kemudharatan.